Direct evidence of initial pitting corrosion - Wang, M; Li, X; Du, N; Huang, Y; Korsunsky, A (2008)
The chloride ion (Cl-) is known as an aggressive species in the aqueous solutions that adsorbs to the imperfect sites on the metal surfaces, such as defects, impurities and second-phase particles. This adsorption process could change the chemical composition and properties, such as ion conductivity, of the passive film. As a result, the passive film becomes less protective and breaks down at some places where the underlying metals are exposed to the electrolyte and dissolved through anodic reaction forming a pit. In the meantime, the hydrolysis (cathodic reaction) occurs inside the pit giving rise to a lower pH and leading to an increased dissolution rate of the metals. Subsequently, more chloride ions migrate into the pit in order to maintain electrical neutrality and adsorb onto the pit surface. The repeating of such process causes the pitting propagation. However, anodic polarization allows the chloride ions to migrate into the passive film more easily. With growth of the pit, more corrosion products make both in plane diffusion across the sample surface and out-of-plane diffusion to bulk solution from the pit mouth [M.G. Fontana, N.D. Greene, Corrosion Engineering, second ed., McGraw-Hill, New York, 1978]. © 2008 Elsevier B.V. All rights reserved.